Multipath TCP-Based IoT Communication Evaluation: From the Perspective of Multipath Management with Machine Learning - Ji, Ruiwen; Cao, Yuanlong; Fan, Xiaotian; Jiang, Yirui; Lei, Gang; Ma, Yong (Sensors (Basel, Switzerland), 2020)
With the development of wireless networking technology, current Internet-of-Things (IoT) devices are equipped with multiple network access interfaces. Multipath TCP (MPTCP) technology can improve the throughput of data transmission. However, traditional MPTCP path management may cause problems such as data confusion and even buffer blockage, which severely reduces transmission performance. This research introduces machine learning algorithms into MPTCP path management, and proposes an automatic learning selection path mechanism based on MPTCP (ALPS-MPTCP), which can adaptively select some high-quality paths and transmit data at the same time. This paper designs a simulation experiment that compares the performance of four machine learning algorithms in judging path quality. The experimental results show that, considering the running time and accuracy, the random forest algorithm has the best performance in judging path quality.